SICONS EFFECTIVENESS ON THE LEVEL OF SATISFACTION OF GUIDANCE AND COUNSELING SERVICES IN MAN 2 BANYUMAS STUDENTS - ALIEF BUDIYONO; NUR AZIZAH; ADHITYA RIDWAN BUDHI PRASETYO NUGROHO (Universitas Islam Negeri Mataram, 2022)
Cyber counseling, as a part of educational institutions, has a role in the study process to find out the problems and obstacles of students to help solve their problems in technological developments. The method in this research is the Mix Method approach to Research and Development. Methods of collecting data through Questionnaire, Observation, Interview, and Documentation on students of MAN 2 Banyumas. This study's results show that SICONS effectively increases student satisfaction in individual counseling services before receiving SICONS services is 55.06. The score after receiving SICONS services is 74.56, supported by the results of the paired difference test, which produces a significant (p-value = 0.000), while the group counseling service before SICONS service was 46.65. The score after receiving SICONS service was 73.08, supported by the results of the paired difference test, which resulted in a significant (p-value = 0.000). So it can be concluded that SICONS is effective in increasing student satisfaction in guidance and counseling services at MAN 2 Banyumas.